Arabic And Contact-Induced Change - Lucas, Christopher; Manfredi, Stefano (My University, 2020)
This volume offers a synthesis of current expertise on contact-induced change in Arabic and its neighbours, with thirty chapters written by many of the leading experts on this topic. Its purpose is to showcase the current state of knowledge regarding the diverse outcomes of contacts between Arabic and other languages, in a format that is both accessible and useful to Arabists, historical linguists, and students of language contact.
Keywords: HUMANITIES and RELIGION::Languages and linguistics::Other languages::Arabic language; historical linguists; contact-induced change